The Impact of Sustainable Growth and Sustainable Environment on Public Health: A Study of GCC Countries - Khan, Mohd Naved; Aziz, Ghazala; Khan, Mohd Saeed (Frontiers in Public Health, 2022)
The current study investigates the impact of economic growth, carbon emission, temperature, and environmental technology on public health in GCC countries. Panel data from 1990 to 2020 is used, and the panel unit root test is used to check the stationarity of the data. After cointegration analysis, the ARDL estimation technique checks the long-run and short-run association between variables. The results have proved that economic growth enhances exposure to PM2.5 and mortality but helps in increasing life expectancy. Likewise, carbon emission also enhances exposure to PM2.5 and mortality but improves life expectancy. As far as temperature is concerned, although it increases the exposure to PM2.5, it also increases life expectancy. It is also found that environmental technology enhances exposure to PM2.5. For policy implication, the study reports that investment in research and development and modifications the energy mix are key measures to enhance the public health in GCC countries.